RIGHT OF MALE HEIRS TO THE ORIGINAL FAMILY RELATED TO NYEBURIN’S MARRIAGE TO LAND RIGHTS IN PERSPECTIVE BALINESE LAW OF CUSTOMS - Anak Agung Ngurah Mukti Prabawa Redi; I Made Suwitra; Putu Ayu Sriasih Wesna (NOTARIIL Jurnal Kenotariatan, 2021)
The marriage of nyeburin changes the position of women into purusa and men into pradana. Then in terms of inheritance, the priority in the nyeburin marriage is the woman, but the status of the man who becomes pradana is questioned when nyeburin marriage ends and the status of the man is returned to his family of origin. This study aims to analyze the inheritance rights of men who do nyeburin’s marriage on inherited land in their origin family and to analyze the implications of inheritance rights of men who do nyeburin’s marriage in right and obligations of origin family. The research method used is normative legal research. In addition, the data collection technique used is the library study technique. The results of this study revealed that (1) a man who does a nyeburin marriage will lose his right to inherit in his family of origin because of a change in his status to pradana in his wife's family. A man who does a nyeburin marriage will be considered to have left kedaton so that he has the same position as a woman who marries out. (2) Burden marriage has implications for the position of the husband so that here the husband follows the wife. The rights and obligations as husband and wife are still the same as in a normal marriage, only in a marriage where the wife's position is higher than that of the husband.